(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Triple negative breast cancer (TNBC) is a divergent disease which lacks receptor for estrogen (ER), progesterone (PR) and human epidermal growth factor receptor 2 (HER2). It constitutes about 15-20% of total breast cancer cases globally which mainly strikes younger women. Due to its aggressive nature, the standard choice of treatment for TNBC is chemotherapy, but the same has very poor prognosis due to risk of tumor recurrence, metastasis and death. To direct the line of research to get pathological Complete Response (pCR) and increase the quality of life (QOL) years of cancer patients, it is necessary to understand the molecular pathways and their down signalling pathways which can be targeted. Triple negative breast cancer involves several signaling pathways leading to tumor initiation, proliferation, and metastasis such as Ras/Raf/MEK pathway, PI3/AKT/mTOR pathway, DNA repair pathway, Wnt/β-catenin Pathway, Hedgehog pathway, Notch signalling pathway and immune pathway. Currently available treatment for triple negative breast cancer comprises chemotherapy in combination which includes anthracyclines, platinum compounds, folate antagonist, taxanes, cyclophosphamide and others. The present review focuses on the molecular aspect of TNBC subtypes and targets. Also, the ongoing clinical trials along with the completed clinical trials targeting different pathways for the treatment of TNBC patients are discussed.